Symposium 4: Using Action-Oriented Or Participatory Research Methods For Research On Networked Learning - Steeples, Christine (Proceedings of the International Conference on Networked Learning, 2004)
This paper explores action-oriented or participatory research in the field of networked learning. A small study was conducted into ways of supporting distributed communities of practitioners in their ongoing professional development, through the creation and use of stored multimedia artifacts within networked learning environments A user-centred, exploratory and participatory research approach was adopted. The paper suggests why such an approach was deemed appropriate for this kind of study: allowing the researcher to build theoretical constructs grounded in qualitative data gathered from real practitioners; but also informed by the researcher’s own personal experiences and self-reflective observations.